SISTEM INFORMASI MANAJEMEN PADA ORGANISASI PENDIDIKAN DASAR - SYAHRUL, SYAHRUL; SUYONO, SUYONO; DEWI, RADENI SUKMA INDRA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This study discusses the stages of planning and organizing in the implementation of the Management Information System (SIM) in schools. The results of the study confirm that careful planning, involving all relevant parties such as teachers, students, principals, and parents, is very important for the successful implementation of driver's licenses. A needs analysis that includes the type of data to be managed as well as budgeting for hardware, software, and technical training is also considered crucial. Furthermore, the organizing stage, which includes the formation of a cross-departmental implementation team and the arrangement of clear operational procedures, greatly determines the smooth implementation process. This study expands on the findings of previous studies by highlighting the importance of data protection and access rules in driver's licenses, aspects that have often been overlooked in previous studies. These findings provide practical guidelines for schools in planning and organizing the implementation of driver's licenses effectively. ABSTRAKPenelitian ini membahas tahapan perencanaan dan pengorganisasian dalam implementasi Sistem Informasi Manajemen (SIM) di sekolah. Hasil penelitian menegaskan bahwa perencanaan yang matang, melibatkan semua pihak terkait seperti guru, siswa, kepala sekolah, dan orang tua, sangat penting untuk keberhasilan implementasi SIM. Analisis kebutuhan yang mencakup jenis data yang harus dikelola serta penetapan anggaran untuk perangkat keras, perangkat lunak, dan pelatihan teknis juga dianggap krusial. Selanjutnya, tahap pengorganisasian yang mencakup pembentukan tim implementasi lintas departemen serta pengaturan prosedur operasional yang jelas sangat menentukan kelancaran proses implementasi. Penelitian ini memperluas temuan studi sebelumnya dengan menyoroti pentingnya perlindungan data dan aturan akses dalam SIM, aspek yang sering terabaikan dalam penelitian terdahulu. Temuan ini memberikan pedoman praktis bagi sekolah dalam merencanakan dan mengorganisir implementasi SIM secara efektif dan aman.